Penguatan Regulasi Hukum untuk Pengelolaan Sampah Berkelanjutan di Pondok Dayung Jakarta Utara - Sodikin, Nur; I Dewanto; Muliansyah, Dadah; Nurhidayah, Rika; Satiadharmanto, Deddi Fasmadhy (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Sustainable waste management has become a major challenge in urban areas, including in Pondok Dayung, North Jakarta. The academic concern in this research relates to the low level of community awareness and the lack of effective regulations for environmentally friendly waste management. The purpose of this research is to strengthen legal regulations in waste management by using the Asset-Based Community Development (ABCD) approach, which emphasizes community empowerment in managing local resources. The methods used in this assistance involved a series of activities, starting with mapping local assets and understanding the challenges and potential within the community. The assistance was carried out over four months, with stages including situational analysis, designing community-based regulations, training and capacity building for the community, and evaluation of the implementation of these regulations. Throughout this process, active participation from the Pondok Dayung community was prioritized, ultimately resulting in a draft of waste management regulations based on local potential and community participation. The results of this activity showed an increase in community awareness of the importance of environmentally friendly waste management and the establishment of regulations that better support environmental sustainability. In conclusion, strengthening legal regulations accompanied by community empowerment can create more effective and sustainable waste management.